EKSPLANASI RITME SIRKADIAN PADA SIKLUS MALAM–SIANG: Perspektif Tafsir Al-Jawahir Karya Tantawi Jawhari - Nur Laili Luthfiyyah; Muhammad Arwani Rofi’i (Jurnal Al I'jaz, 2025)
The circadian rhythm is a natural biological cycle of the human body that operates over approximately 24 hours and is strongly influenced by light. In the context of modern life, lifestyle disruptions such as staying up late and sleep–wake inversion increasingly distance humans from the natural night–day rhythm, thereby affecting physical and mental health. Departing from this problem, this study examines the phenomenon of night and day in the Qur’an through the perspective of the scientific exegesis (tafsir ilmi of Tantawi Jawhari, a Qur’anic exegete known for his strong emphasis on the relationship between ayat kawniyyah and scientific knowledge. This study aims to describe Tantawi Jawhari’s interpretation in Al-Jawahir fi Tafsir Al-Qur’an Al-Karim of Qur’anic verses concerning the creation of night and day and to analyze their relevance to the concept of circadian rhythm within chronobiological studies. The research employs a qualitative library research method using a thematic (mawdui) approach to Qur’anic interpretation. Primary data consist of Qur’anic verses related to night and day, such as Q.S. al-Anam [6]: 60, Q.S. al-Furqan [25]: 47, Q.S. al-Qasas [28]: 73, and Q.S. al-Rum [30]: 23, along with their interpretations in Al-Jawahir. Data analysis is conducted through a descriptive–analytical method by presenting Jawhari’s interpretations and subsequently examining their conceptual relevance to the human circadian rhythm. The findings indicate that, in Tantawi Jawhari’s perspective, the creation of night and day is understood as a manifestation of divine mercy that sustains the order of human life. Night is positioned as a time for rest that enables tranquility and bodily recovery, while daytime is designated for activity supported by sunlight. This interpretation demonstrates a conceptual correspondence with the principles of the circadian rhythm, in which disruption of appropriate rest–activity patterns may lead to physical and psychological disorders. Accordingly, this study affirms that the scientific exegesis of Tantawi Jawhari provides a Qur’anic framework relevant for reflecting on the importance of maintaining the circadian rhythm as part of sunnatullah in human life.